Antibacterial Activity of Honeybee Venom Against Pathogenic Bacteria in Comparison with Common Antibiotics - Gavanji, Shahin; Bakhtari, Azizollah (Makara Journal of Science, 2023)
Antibiotic resistance has dramatically spread in recent decades and has become a serious problem in modern medicine. Honeybee venom or bee venom (BV) has anticancer, anti-inflammation, and antimicrobial properties. This study aimed to evaluate the influence of BV on certain pathogenic bacteria. The effects of different concentrations of BV against Klebsiella pneumonia, Pseudomonas aeruginosa, and Staphylococcus aureus were evaluated by disk diffusion method (inhibition zone, IZ), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Additionally, the antibacterial activity of BV was compared with that of ampicillin, penicillin, and tetracycline. The results indicated that different concentrations of BV had an inhibitory effect on the pathogen species. The MIC and MBC of BV were 18 and 24 μg/mL for K. pneumonia, respectively, 38 and 42 μg/mL for P. aeruginosa, respectively, and 21 and 31 μg/mL for S. aureus, respectively. Among the bacterial species tested, BV was the most effective against K. pneumonia. Meanwhile, P. aeruginosa was the most resistant against BV. The comparison revealed that 100 μg/mL BV had a greater effect on IZ against P. aeruginosa and K. pneumonia compared with evaluated common antibiotics (p < 0.05). This study showed that BV demonstrated antibacterial effects. Precise toxicology examinations are required for the development of new antibiotics.